2012
DOI: 10.3171/2012.4.peds1253
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome for endoscopic third ventriculostomy alone or in combination with choroid plexus cauterization for congenital aqueductal stenosis in African infants

Abstract: Object The authors have previously reported on the overall improved efficacy of endoscopic third ventriculostomy (ETV) combined with choroid plexus cauterization (CPC) for infants younger than 1 year of age. In the present study they specifically examined the long-term efficacy of ETV with or without CPC in 35 infants with congenital aqueduct stenosis treated at CURE Children's Hospital of Uganda during the years 2001–2006. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 112 publications
(70 citation statements)
references
References 14 publications
0
70
0
Order By: Relevance
“…Both types of neuroendoscopes are used across centers in North America for ETV/CPC, with reported 12-month success rates ranging from 38% for rigid neuroendoscopy 20 to 57% for flexible neuroendoscopy. 8 In Africa, Asia, and Europe, both flexible neuroendoscopy 1,5,9,10,14,15,19 and rigid neuroendoscopy 2 have been used, with no consensus on the superiority of either technique. A retrospective review of ETV/CPC treatment outcomes from multiple North American centers participating in the Hydrocephalus Clinical Research Network suggested that greater extent of CPC and the use of a flexible neuroendoscope were associated with improved success, although the sample size was small and the patients were not randomized to neuroendoscopy type.…”
Section: 9-11mentioning
confidence: 99%
“…Both types of neuroendoscopes are used across centers in North America for ETV/CPC, with reported 12-month success rates ranging from 38% for rigid neuroendoscopy 20 to 57% for flexible neuroendoscopy. 8 In Africa, Asia, and Europe, both flexible neuroendoscopy 1,5,9,10,14,15,19 and rigid neuroendoscopy 2 have been used, with no consensus on the superiority of either technique. A retrospective review of ETV/CPC treatment outcomes from multiple North American centers participating in the Hydrocephalus Clinical Research Network suggested that greater extent of CPC and the use of a flexible neuroendoscope were associated with improved success, although the sample size was small and the patients were not randomized to neuroendoscopy type.…”
Section: 9-11mentioning
confidence: 99%
“…ETV resulted in satisfactory posterior fossa surgical conditions. ETV has been shown to offer an acceptable low cost alternative treatment to shunts especially in children with obstructive hydrocephalus in developing countries [20,21]. There are numerous studies now confirming the high success rate and low complication rate of ETV.…”
Section: Discussionmentioning
confidence: 96%
“…The study by Warf et al proved the difference in the success rate with 48.6% in patients in whom they practiced only ETV compared to 81.9% in those in whom they practiced ETV and plexus coagulation both. 51 Kulkarni et al 52 reported the relative higher risk of initial failure in ETV than shunt in children. The relative risk becomes progressively lower for ETV after about 3 months.…”
Section: Discussionmentioning
confidence: 99%